2020
DOI: 10.3390/ijerph17238901
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Evaluation of the Guilt and Shame Experience Scale (GSES) on a Representative Adolescent Sample: A Low Differentiation between Guilt and Shame

Abstract: The Guilt and Shame Experience Scale (GSES) is a new, brief self-report instrument for assessing experiences of guilt and shame. It includes two distinct scales: feelings of shame and feelings of guilt. The present report focuses on results from a final validation study using a nationally representative sample of 7899 adolescents (M age = 14.5 ± 1.1 years, 50.7% boys) who participated in the 2014 Health Behavior in School-aged Children study. For factor analysis, the dataset was divided into two groups. One gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…This idea may have relevant implications when establishing interventions with both children and adolescents suffering from and exerting bullying. Somehow related to this study, Malinakova et al [11] revealed in a study that adolescence is a developmental period involving low differentiation between moral emotions like guilt and shame compared with adulthood. This is relevant in order to understand the different behaviors, attitudes, and profiles related to bullying [12].…”
supporting
confidence: 54%
“…This idea may have relevant implications when establishing interventions with both children and adolescents suffering from and exerting bullying. Somehow related to this study, Malinakova et al [11] revealed in a study that adolescence is a developmental period involving low differentiation between moral emotions like guilt and shame compared with adulthood. This is relevant in order to understand the different behaviors, attitudes, and profiles related to bullying [12].…”
supporting
confidence: 54%
“…This correlation is consistent with the original paper of ASPS (Simonds et al, 2016), showing that all three components of ASPS measure domains related to adolescent shame. To explain these correlations, several studies have confirmed that shame and guilt differ despite the overlap (dos Santos et al, 2020; Malinakova et al, 2020), as shame is associated with a negative self‐evaluation in general attributions, whereas guilt is characterized by a particular behavior (Szentágotai‐Tătar et al, 2015). The difference between shame and guilt in the present study was not as considerable as in the original article by ASPS (Simonds et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…TOSCA scales using fixed scenarios, asking the respondent about everyday situations associated with feelings of guilt or shame (J. Tangney et al, 2000). Scenario‐based scales are time‐consuming (Malinakova et al, 2020), and several studies agree that shame‐provoking situations are not universal and fixed. Also, apart from everyday situations considered in the TOSCA scales, shame may arise from appearance, personality traits, or the mistreatment of others (Simonds et al, 2016; J. P. Tangney & Dearing, 2011), and it is highly culture‐dependent (Gottzén, 2016; Mayer & Vanderheiden, 2019; Mayer & Viviers, 2017; Schitter, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations